Potensi Beberapa Tumbuhan Sebagai Anti Inflamasi di Indonesi - Mutiara, Sephia Aruma; Damayanti, Ervina; Wardhana, M. Fitra; Sukohar, Asep (CV. Jasa Sukses Abadi, 2024)
Inflammation is a biological response of the immune system that can be triggered by various factor including pathogens, physical trauma and toxic compounds. Prolonged consumption of NSAID as an anti-inflammatory can caused some serious side effects for the body. As a result, many people has switched to using plants as therapy. Another reason for choosing therapy with plants is more affordable, as well as family traditions trust in the efficacy of a plant. The purpose of this review article is to provide information about several medicinal plants that have anti-inflammatory activity. The method in this study was a systematic literature review which is traced through database, Google Scholar and Pubmed. The literature used was published in 2019 to 2024 and 11 journals were obtained as primary data. Some plants studied as anti-inflammatory are red spinach (Amarathus tricolor L.), Beligo (Benincasa hispida (Thunb.) Cogn.), Pineapple (Ananas Comosus (L.) Merr.), Kecapi (Sandoricum koetjape (Burm.f. ) Merr., Sesewanua (Clerodendrum squamatum Vahl.), Turmeric (Curcuma domestica Val.), Aloe vera (Aloe vera L), Tamarind (Tamarindus indica L.), Green grass jelly (Cyclea barbata Miers.) and Galangal (Kaempferia galangal L.). In research on the anti-inflammatory activity of several plants studied, it was proven to be able to improve several inflammatory parameters, but at different doses because it depended on the response of the test animals and the secondary metabolite content of each plant.